The Effect of Mind Mapping Learning Model on Student Cognitive Learning Outcomes in Natural Science Subjects in Grade IV Elementary School - Mardiana Sari; Siti Sarah; Emi Sulistri; Evinna Cinda Hendriana (Universitas Pendidikan Indonesia (UPI), 2021)
This study aims to determine the effect of using the mind mapping learning model on the cognitive learning outcomes of students in the science subject of sound material. The results of this study indicate that; (1) There is an effect of student cognitive learning outcomes between the class that is given the mind mapping learning model and the class that is given direct learning on sound science subjects, the results of the hypothesis test show that the value of t_(count = ) 3.8330 t_(table = ) 1.6786 for = 5% and dk = 46. (2) Mind mapping learning model has a high influence on students' cognitive learning outcomes on sound material, the result of calculating the effect size in this study is E_s=1.00 0.8 are high criteria. (3) There is a positive response to the mind mapping learning model, the results of the calculation of the percentage of student responses show an average of 84% in the very good category. Thus it can be concluded that the mind mapping learning model can affect students' cognitive learning outcomes and make it easier for students to understand the material.